Pengembangan LKPD Berbasis Etnomatematika pada Arsitektur Pura Mandhara Giri Semeru Agung - Bunga, Shanty Bunga Adinda; Firdaus, Hana Puspita Eka; Fatqurhohman, Fatqurhohman (Mandalika Mathematics and Educations Journal, 2025)
The urgency of this study lies in the importance of integrating local culture into mathematics learning to create a learning experience that is contextual, meaningful, and relevant to the students' environment. The ethnomathematics approach is seen as an effective strategy to learn mathematical concepts through local wisdom while fostering appreciation for culture. This study aims to develop a Student Worksheet (LKPD) based on ethnomathematics, using the architectural context of Pura Mandhara Giri Semeru Agung, focused on geometric transformations for 11th-grade high school students. The method used is Research and Development (R&D) with the ADDIE model, which includes analysis, design, development, implementation, and evaluation stages. The instruments consist of validation sheets to measure the product's feasibility, teacher interviews, and student response questionnaires to assess practicality. The validation results show a validity level of 98.335% (categorized as very valid), student practicality at 88.45%, and teacher response at 97.50% (very practical). In conclusion, this ethnomathematics-based worksheet is feasible for use in mathematics and effective for learning geometric concepts integrated with local culture. Further research is recommended to test its effectiveness in improving learning outcomes and cultural appreciation across different educational levels.